The Effect of Sponsorship and Customer Engagement Program in Improving Brand Awareness (Case Study of Nike as The Official Sport Apparel of The Indonesian National Team) - Miranda Laditya Magdalena; Agus Dharmanto (Kusuma Negara Business School, 2020)
Soccer is a fairly large sport in Indonesia, this makes the companies compete to become sponsors of this one sport. In this study the results show that sponsors do not have a significant influence on brand awareness, customer engagement programs have an influence on brand awareness, then sponsors and customer engagement programs related to brand awareness. This research is expected to contribute to the academic field and become an additional reference for other researchers interested in the field of special sponsors in the field of sports.